ON THE PALEOFAUNA INVERTEBRATES (MOLLUSCA, ARTROPODA; INSECTA) OF DIATOMITE DEPOSITS OF SHAMB–1 LOCALITY (SISIAN SUITE, EARLY PLEISTOCENE, ARMENIA) - М. A. Маrjanyan; R. G. Harutyunyan; L. J. Harutyunova; I. G. Gabrielyan (Юг России: экология, развитие, 2016)
Aim. The study of fossil insects from diatomaceous sediments of Shamb-1 locality of Sisian Suite (Early Pleistocene). The collection of fossils plants and animals of Institute of Botany of NAS RA and authors' findings served as material for study.Methods. The material is processed and prepared for study by conventional methods in paleontology for prints and fossils of insects from diatomaceous sediments. There are 654 samples studied: 2 samples were with mollusks’ imprints and 652 samples with imprints of insects, from which preserved marks on 291samples allowed to identify them up to order, family, genus and species.Results. The studied material refers to the Mollusca and Arthropoda (Insecta) types. Insects are represented by species of orders Orthoptera (2 fam.), Homoptera (1 fam.), Heteroptera (2 fam.), Coleoptera (15 fam.), Hymenoptera (2 fam.), Diptera (1 fam.). Coleopteras dominate among them and are presented with following species of the family – Carabidae, Dytiscidae, Hydrophilidae, Histeridae, Staphylinidae, Silphidae, Elateridae, Buprestidae, Lampyridae, Scarabaeidae, Chrysomelidae, Tenebrionidae, Coccinellidae, Cerambycidae, Curculionidae.Main conclusions. An analysis of the taxonomic composition of paleofauna was done, which corresponds to the recent fauna and with considering modern ecological characteristics of systematical groups and species. In the investigated location of Shamb-1 a version is suggested about the palaeolandscapes and palaeoclimate in the Early Pleistocene.